2003
DOI: 10.1016/s0928-8244(03)00166-4
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of mycobacterial antigen-induced proliferation and interferon-γ responses in peripheral blood mononuclear cells of tuberculosis patients upon effective chemotherapy

Abstract: Peripheral blood mononuclear cells (PBMC) were obtained from culture-proven tuberculosis (TB) patients before and after 2 and 6 months of chemotherapy with a multi-drug regimen. PBMC were tested for cellular responses in antigen-induced proliferation and interferon-gamma (IFN-gamma) assays in response to complex mycobacterial antigens (whole cell Mycobacterium bovis BCG and M. tuberculosis, cell walls and short-term culture filtrate [ST-CF] of M. tuberculosis), fractionated ST-CF antigens (fractions F1-F10) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
48
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 27 publications
10
48
0
1
Order By: Relevance
“…A previous study [7] showed that after 2 months of treatment T-cells proliferation response was restored to the same level as 6 months after, without a linear relationship: however, this study was based on only 15 patients. Our study performed on a significantly larger number of individuals and the method of data collection (random assignation to the month of assay) and statistical analysis (random effect model) allowed a more accurate estimation of changes over time.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…A previous study [7] showed that after 2 months of treatment T-cells proliferation response was restored to the same level as 6 months after, without a linear relationship: however, this study was based on only 15 patients. Our study performed on a significantly larger number of individuals and the method of data collection (random assignation to the month of assay) and statistical analysis (random effect model) allowed a more accurate estimation of changes over time.…”
Section: Discussionmentioning
confidence: 81%
“…According to this hypothesis, other studies have shown that CD4+ T cells responsive to a large array of MTB epitopes are compartmentalised at the site of the disease, appearing in the peripheral blood after effective chemotherapy which reverses the state of relative hypoanergy usually observed in these patients [24,25]. Other contributing factors in the restoration of cellular response could be the shift in cytokine production by mononuclear blood cells [7,10,26].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Although, these genes have only 10-35% homology to esat6, they are approximately of the same size (ca 100 aa) and share a similar genomic organization. Because of the immunodominance of ESAT-6 (ESXA) [12][13][14][15][16][17][18], other ESAT-6 family proteins have also received considerable attention for immunological evaluation [19][20][21]. As given below, the genes of some of these proteins are present in M. tuberculosis-specific genomic regions, and therefore they have been considered useful in the diagnostic and vaccine applications [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%